Teaching students with special educational needs in inclusive music classrooms: experiences of music teachers in Hong Kong primary schools. (2nd April 2016) - Wong, Marina Wai-yee; Chik, Maria Pik-yuk
Abstract : It has been a decade since the implementation of Hong Kong's policy of inclusion, that mainstream schools should admit students with special educational needs (SEN). This study reports on music teachers' experiences of teaching SEN students in inclusive music classrooms. Data were derived from a qualitative multiple case study comprising10 government-funded primary school music teachers. These music teachers lack knowledge of ways to support the musical development of pupils with SEN and reported learned helplessness and effective exclusion of SEN students. The major barrier to effective inclusive music teaching evidenced is the absence of in-service training in inclusive music education.